Difficulties concerning Diabetes Mellitus Type 1 in children and adolescents - Tatiana Rebouças Moreira; Samila Torquato Araújo Bandeira; Synara Cavalcante Lopes; Silvana Linhares de Carvalho; Francisca Diana da Silva Negreiros; Clarice da Silva Neves (Universidade Federal do Ceará, 2016)
Objective: to evaluate the knowledge on diabetes in children and adolescents and the difficulties regarding the disease. Methods: a quantitative study with 40 patients from 6 to 17 years older who were subjected on a questionnaire based on self-care behaviors proposed by the American Association of Diabetes Educators. Results: the average age was 11.6 years with predominance of the female gender (57.5%), most attending grade school (80.0%), naming the parents as primary caregivers (72.5%). Regarding the knowledge about the disease, the item with the highest percentage of errors was about the pathophysiology of Diabetes Mellitus type 1. On the difficulties related to the treatment, food control and application of insulin had higher frequency. Conclusion:the study revealed a high percentage of correct answers among the participants, suggesting knowledge about the disease. Nevertheless, they reported food control and insulin therapy as the main difficulties related to treatment.